2023
DOI: 10.1177/19476035231154511
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Transcriptome Changes in Osteoarthritis: Gene Expression, Pathways and Alternative Splicing

Abstract: Objective Osteoarthritis (OA) is the most prevalent joint disease characterized by the degeneration of articular cartilage and the remodeling of its underlying bones, resulting in pain and loss of function in the knees and hips. As far as we know, no curative treatments are available except for the joint replacement. The precise molecular mechanisms which are involved in the degradation of cartilage matrix and development of osteoarthritis are still unclear. Design By analyzing RNA-seq data, we found the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The difference between our study and the study by Katsoula et al is that we analyzed genome-wide differential splicing between healthy and OA cartilage. Furthermore, the study by Li et al 12 and our study indicated that there are many DASEs related to ECM-related pathways between healthy controls and individuals with OA. Li et al identified TIA1 as a key regulator of these DASEs.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The difference between our study and the study by Katsoula et al is that we analyzed genome-wide differential splicing between healthy and OA cartilage. Furthermore, the study by Li et al 12 and our study indicated that there are many DASEs related to ECM-related pathways between healthy controls and individuals with OA. Li et al identified TIA1 as a key regulator of these DASEs.…”
Section: Discussionsupporting
confidence: 68%
“…2). With the exception of HK2 and ANGPTL4, most of the differentially expressed genes were also identified in the analysis by Li et al 12 . Then, to identify dysregulated splicing regulators related to hyaline cartilage fibrosis, we aggregated a comprehensive list of 452 splicing regulators from different sources, including previous publications [13][14][15][16][17] and the SpliceAid2 database 18 .…”
Section: Identification Of Ddx5 As a Downregulated Gene And Protein I...mentioning
confidence: 90%
“…Although no identity was observed between this gene and the previously proposed candidates ( Song et al, 2004 ; Lemay et al, 2023 ), it is annotated as an isopropylmalate synthase, a homolog to L1 , the eucomic acid synthase ( Lyu et al, 2023 ). It recently came to our attention that the same gene that we identified as L2 was also identified for L2 in a non-peer-reviewed preprint ( Li et al, 2023 ). This work is in accordance with our identification and multiple CM prediction and might be a valuable confirmation of our analyses.…”
Section: Discussionmentioning
confidence: 78%
“…Based on the highest average accuracy, we identified Glyma.03G005700 as the candidate gene for L2 , annotated as isopropylmalate synthase (IPMS; similar to the eucomic acid synthase GLYMA.19G120400). This gene has been identified as an L2 candidate in a preprint ( Li et al, 2023 ); it is a homolog to the cloned L1 Glyma.19G120400 ( Lyu et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…69 the diagnosis of osteoarthritis. The analysis of Li et al (2023) has uncovered that ADM is evidently down-regulated in osteoarthritis. Additionally, existing studies have shown that ADM is regulated by tumour necrosis factor α and changes in ADM expression can affect adipogenesis and osteogenesis, providing new strategies for the treatment of bone and joints (Uzan et al, 2006;Hopwood et al, 2009;Qi et al, 2020;Cao et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%